Anti-Cancer Activity Based on the High Docetaxel Loaded Poly(2-Oxazoline)s Micelles - Xu M (Dove Medical Press, 2021)
Min Xu,1,2,* Chong Yao,3,* Wei Zhang,1 Shen Gao,1 Hao Zou,1 Jing Gao1,4 1School of Pharmacy, Second Military Medical University, Shanghai, 200433, People’s Republic of China; 2Department of Pharmacy, Changzheng Hospital, Shanghai, 200003, People’s Republic of China; 3Clinical Pharmacy Center, Department of Pharmacy, Chinese PLA General Hospital, Beijing, 100850, People’s Republic of China; 4State Key Laboratory of Toxicology and Medical Countermeasures, Beijing Institute of Pharmacology and Toxicology, Beijing, 100850, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jing Gao; Hao ZouSchool of Pharmacy, Second Military Medical University, No. 325 Guohe Road, Yangpu District, Shanghai, People’s Republic of ChinaTel +86-10-6687-4665Email gjsmmu@126.com; haozou@smmu.edu.cnPurpose: Nanocarriers, with a high drug loading content and good safety, to achieve desirable therapeutic effect are always the goals for industry and research.Methods and Results: In the present study, we developed a docetaxel loaded poly-2-oxazoline polymer micellar system which employed poly-2-butyl-2 oxazoline and poly-2-methyl-2 oxazoline as the hydrophobic chain and hydrophilic chain, respectively. This micellar system achieves a high load up to 25% against the docetaxel, and further demonstrates an IC50 as low as 40% of the commercialized docetaxel injection in vitro and a double maximum tolerated dose in MCF-7 cells in vivo.Conclusion: The high drug loading content, superior safety, and considerable anti-cancer activity make this newly developed docetaxel loaded poly(2-oxazoline) micelle go further in future clinical research.Keywords: poly(2-oxazoline)s, micelle, docetaxel, high loading, anti-cancer activity